Pengaruh Mineral Sekunder Sulfat Hasil Oksidasi Pirit Terhadap Nilai Total Sulfur Pada Batubara Formasi Haloq dan Serpih Karbonan Formasi Batuayau Cekungan Kutai Atas - Annisa Annisa (PROMINE, 2016)
Four samples of coal and two samples of carbonaceous shales at the Latest Eosen age were studiedabout the minerals contains relative to height of average sulphur values. The sulphur in coal Haloqformation samples are code HBG-1102 (3,55% adb), MMH- 0504 (0,95% adb), MMH- 05021 (0,91%adb), MDG-0703 (0,7% adb) and the sulphur in carbon shale Batuayau formation samples are codeMRH-0806 (0,35% adb) and MRH-0801 (3.25% adb). The two group of rock samples contain highsulphur with average 1,53% (adb) in Haloq formation and 1,78% (adb) in Batuayau formation. Analysisproximate, ultimate, and x-ray diffraction (XRD) were used for determine the coal compositions, thevalue of carbon (C), hidrogen (H), oxygen (O), Nitrogen (N), and sulphur (S), and expectation ofminerals in coal. The results of XRD were showed mineral zaherite, quartz, caolinite, beidelite weretransformed from smectite, and mineral nacrite were transformed from caolinite. Melanterite andmagnesiocopiate were secondary mineral of sulphate were indicated formed from oxidation pyriteinfluence. The presence of Melanterite and magnesiocopiate were indicated as caution of the highestaverage sulphur value in coal and carbonaceous shale samples.